The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2023
DOI: 10.15252/embj.2022113033
|View full text |Cite
|
Sign up to set email alerts
|

A mitochondrial SCF‐FBXL4 ubiquitin E3 ligase complex degrades BNIP3 and NIX to restrain mitophagy and prevent mitochondrial disease

Abstract: Mitophagy is a fundamental quality control mechanism of mitochondria. Its regulatory mechanisms and pathological implications remain poorly understood. Here, via a mitochondria-targeted genetic screen, we found that knockout (KO) of FBXL4, a mitochondrial disease gene, hyperactivates mitophagy at basal conditions. Subsequent counter screen revealed that FBXL4-KO hyperactivates mitophagy via two mitophagy receptors BNIP3 and NIX. We determined that FBXL4 functions as an integral outer-membrane protein that form… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
37
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(48 citation statements)
references
References 55 publications
3
37
0
Order By: Relevance
“…Early studies identified transcriptional regulation by hypoxia-inducible factor 1 (HIF-1) as a key facet of BNIP3 and NIX regulation 4 . Consistent with this model, both BNIP3 and NIX expression and associated mitophagy are potently induced upon hypoxia onset 14 . Recently, multiple groups have extended this model, reporting that the ubiquitin-proteasome system (UPS) potently restricts BNIP3 and NIX levels to further curb mitophagy [12][13][14][15][16][17] .…”
Section: Introductionsupporting
confidence: 66%
See 3 more Smart Citations
“…Early studies identified transcriptional regulation by hypoxia-inducible factor 1 (HIF-1) as a key facet of BNIP3 and NIX regulation 4 . Consistent with this model, both BNIP3 and NIX expression and associated mitophagy are potently induced upon hypoxia onset 14 . Recently, multiple groups have extended this model, reporting that the ubiquitin-proteasome system (UPS) potently restricts BNIP3 and NIX levels to further curb mitophagy [12][13][14][15][16][17] .…”
Section: Introductionsupporting
confidence: 66%
“…Consistent with this model, both BNIP3 and NIX expression and associated mitophagy are potently induced upon hypoxia onset 14 . Recently, multiple groups have extended this model, reporting that the ubiquitin-proteasome system (UPS) potently restricts BNIP3 and NIX levels to further curb mitophagy [12][13][14][15][16][17] . In light of these concepts, it is important to develop a unified understanding of how steady-state levels of these mitophagy receptors are established and maintained, and how this regulation governs underlying cell physiology.…”
Section: Introductionsupporting
confidence: 66%
See 2 more Smart Citations
“…It is this latter scenario that appears to underlie a rare form of mitochondrial disease characterised by a mutation in FBXL4, the substrate binding component of a particular cullin‐RING E3 ubiquitin ligase (CRL) (Alsina et al , 2020). Three new EMBO Journal publications have now elucidated the mechanism behind how FBXL4 regulates mitophagy, shedding light on the pathology of this debilitating disease and opening potential therapeutic opportunities (Cao et al , 2023; Elcocks et al , 2023; Nguyen‐Dien et al , 2023).…”
Section: Figure Fbxl4 Represses Mitophagy By Controlling Mitochondria...mentioning
confidence: 99%